A CLINICAL STUDY ONMRIDVIKA RAAG (CHUTNEY/SAUCE): A PATHYA AHARA KALPANA (WHOLESOME FOOD PREPARATION) IN THE MANAGEMENT OF ARUCHI (ANOREXIA) - Mannat Marwaha,; Sachin Yadav, (International Journal of Ayurveda and Pharma Research, 2020)
Anorexia is the third most common chronic illness among adolescents and is associated with almost every disease as a first symptom to be reflected. Aruchi (anorexia) is recognized as separate disease and also as symptom of various diseases in Ayurveda. Agnimandya (decreased digestive fire) precedes Aruchi. One needs to correct Agni to treat Aruchi. Intake of Pathya Ahara (wholesome diet) as daily dietary item is must to provide day to day body needs in healthy and diseased both. Raag-Shadav’s are one of the Pathya Ahara (wholesome food) described in Aruchi and Agnimandya. Acharya Charak has mentioned Mridvika Raag as Rochana (interest in food) and Deepana (increases hunger) which is taken as Pathya-Ahara in this study. Total thirty four volunteers were studied (of which 04 were dropouts) and on observation 72.72%, 70.58%, 35.71%, 80.00%, 51.06%, 62.50%, 69.23%, 76.78% and 89.09% improvement was observed in Dantharsha (sensitive tooth), Karshavakrata (astringent taste of mouth), Pootivakrata (foul smell), Katu-Amla-Lavana Vakrata (bitter-sour-salty taste of mouth), Mukhmadhurya (sweetness of mouth), Mukhpaichilya (sliminess in mouth), Anekrasavakrata (presence of different/mixed tastes in mouth), Aagantuja Aruchi (anorexia due to disease), Agnimandhya (decreased digestive fire) respectively which was statistically highly significant.